2013
DOI: 10.1029/2012jb009339
|View full text |Cite
|
Sign up to set email alerts
|

Permanent fore‐arc extension and seismic segmentation: Insights from the 2010 Maule earthquake, Chile

Abstract: [1] Geologists have long known that young normal faults are an important structural element of the Andean Coastal Cordillera, but their relationship to the subduction seismic cycle is still unclear. Some of the largest aftershocks of the 2010 M w 8.8 Maule earthquake in central Chile were nucleated on upper plate normal faults, including the M w 6.9 and 7.0 events of the Pichilemu earthquake sequence. We use the available coseismic GPS displacements, moment tensor sums, and slip distribution models for the Mau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
75
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 140 publications
4
75
0
Order By: Relevance
“…Two recent great subduction earthquakes (M w 8.8 Maule, Chile, in A.D. 2010; M w 9.1 Tohoku-Oki, Japan, in 2011) and associated upper plate aftershocks have underscored the importance of crustal faulting triggered by megathrust events (Aron et al, 2013;Toda and Tsutsumi, 2013). However, the possibility that a foreshock on an upper plate fault might contribute to triggering a subduction great earthquake has never been clearly documented.…”
Section: Introductionmentioning
confidence: 98%
“…Two recent great subduction earthquakes (M w 8.8 Maule, Chile, in A.D. 2010; M w 9.1 Tohoku-Oki, Japan, in 2011) and associated upper plate aftershocks have underscored the importance of crustal faulting triggered by megathrust events (Aron et al, 2013;Toda and Tsutsumi, 2013). However, the possibility that a foreshock on an upper plate fault might contribute to triggering a subduction great earthquake has never been clearly documented.…”
Section: Introductionmentioning
confidence: 98%
“…The best known of these, the Pichilemu sequence, which began 12 days after the main event, cut the entire crust of the forearc as shown by local and regional seismic network data and modeling of geodetic data (Farías et al, 2011;Ryder et al, 2012;Aron et al, 2013). Curiously, Melnick et al (2012) show the Pichilemu structure as a fault of "unconstrained kinematics" in their fi gure 1A.…”
mentioning
confidence: 99%
“…Melnick et al (2006) also show numerous examples of reactivated faults interpreted on their seismic profi les. Given the distribution of slip during the Maule rupture, the northeast strike and relatively steep dip of the SMFS make it almost ideally oriented for co/post-seismic reactivation as a normal fault (Aron et al, 2013). Thus, it would appear to us that a simpler and more straightforward interpretation of the Isla Santa María normal fault ruptures associated with the Maule event is that they are the surface expression of extensional reactivation of SMFS, which is active as a reverse fault during interseismic periods but, like most of the rest of the forearc, is stretched during coseismic rebound.…”
mentioning
confidence: 99%
“…The inference of Allmendinger et al that plate-boundary slip makes the SMFZ "almost ideally oriented for co/post-seismic reactivation as a normal fault" is based on Aron et al (2013). But using coseismic Coulomb stress increments they concluded that "a negative stress fi eld offshore suggests enhanced development of reverse faulting, which agrees with the observations of Melnick et al (2012)" (paragraph 33 of .…”
mentioning
confidence: 82%
“…Indeed, this inference is consistent with most slip in zone B and supports coseismic reverse motion along the SMFZ. Aron et al (2013) proposed that regional normal faulting is associated with permanent extension driven by megathrust-earthquake slip. Unfortunately, their compilation of normal faults contains major biases.…”
mentioning
confidence: 99%